The Efforts to Increase Children's Activeness in Responding to Stories From God's Word Using Discussion Method (Qualitative Study at the Sunday School of the Batu Hidup Christian Church, Jakarta) - Tafetin, Krisna Karolina; Mulyani, Sri (MAHABBAH: Journal of Religion and Education, 2024)
This study aims to explore the role of discussion methods in increasing the activity of small class children in understanding and applying the teachings of the Lord's word that the Sunday school teacher conveys. Discussion methods give children opportunities to interact, share opinions, and discuss the Lord's word stories with their peers. In this process of discussion, children can learn to understand and apply the teachings of the Lord's word in everyday life. This study uses qualitative methods. Collect data by direct observation and structured interviews with a Sunday school teacher. Studies indicate that effective discussion methods promote children's activation. Children involved in discussions are more actively participating, have better understanding, and are able to apply the teachings of the Lord's word in everyday life.